(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study to evaluate our anesthesia experiences and the effect of anesthesia methods performed on maternofetal outcomes in pregnant women diagnosed with COVID-19 who underwent caesarean delivery. Materials and Methods: In this retrospective and cross-sectional study, 67 pregnant women with COVID-19 infection and had a caesarean delivery in our hospital between 01.04.2020-01.01.2021 were included. Age, body mass index score, gestational week, previous cesarean history, comorbidity, symptoms, laboratory values and radiological images were recorded. Type of anesthesia, emergency or elective cesarean was reported. Hospitalization time, complications, need for high frequency oscillation ventilation, continuous positive airway pressure, mechanical ventilation, intensive care unit need and mortality were evaluated. Gender, height, weight, APGAR scores, premature birth and fetal death were recorded. Results: The mean age of the patients was 30.9±6.5years and the body mass index value was 31.7±2.8. The preterm delivery occurred in 25 patients (37.3%). Four (6%) pregnant women had intrauterine ex fetus. Spinal anesthesia was performed to 61 patients (91.0%) and general anesthesia was performed to 6 patients(9.0%). In the pre-cesarean period, 33 patients were asymptomatic (49.3%), 9 patients had fever(13.4%), 32 patients had cough(47.8%), 25 patients had dyspnea(37.3%) and 15 patients had tachypnea(22.4%). Thirty-seven (55.2%) patients had lung involvement on computed tomography. 21(31.3%) patients needed ICU admission. Mortality occurred in 4(5.98%) pregnant women. Further analysis patients undergoing general anesthesia had a higher need for ICU, HFOV, CPAP and invasive mechanical ventilation and a higher maternal mortality rate. Conclusions: Spinal anesthesia is safer for pregnant women with COVID-19 than general anesthesia in terms of maternal and neonatal health. Especially in pregnant women with COVID-19 with pulmonary involvement, general anesthesia should be avoided as much as possible, as it may increase the likelihood of requiring invasive mechanical ventilation, exacerbation of respiratory symptoms and cause more respiratory complications.